Improving service delivery for neuromuscular diseases: a survey of consumers at a tertiary Australian hospital. Issue 12 (5th December 2018) - Anderson, James; Tay, George; Denby, George; Robinson, Jan; Douglas, James; Robinson, Peter; Curtin, Deanne
Abstract: Patients with neuromuscular diseases benefit from coordinated multidisciplinary care to achieve best outcomes. The integration of multi‐specialty healthcare delivered in a single clinic can be challenging for service providers due to cost and resource limitation. Our cross‐sectional survey of 53 adult patients with neuromuscular disease across Queensland revealed only 27% support the introduction of an integrated multidisciplinary clinic. The most cited reason for opposition to a multidisciplinary clinic was a perceived loss of contact with one's usual doctor. Modifying service delivery in neuromuscular disease is a complex undertaking and will need input from numerous stakeholders.